PENGARUH PEMBERIAN INFORMASI PRA BEDAH TERHADAP TINGKAT KECEMASAN PADA PASIEN PRA BEDAH MAYOR DI BANGSAL ORTHOPEDI RSUI KUSTATI SURAKARTA - Endang Sawitri; Agus Sudaryanto (Jurnal Berita Ilmu Keperawatan, 2008)
The background of this research is the invention of particular phenomena, which the patient is on anxiety feeling at pre surgery stage, particularly the femur fracture patient on the orthopedic ward RSUI Kustati Surakarta. While, the aim of this study is to find the influence of delivering information pre surgery through the rate of decreasing patient anxiety before surgery. This research is planed as the experimental research at the type of one group pre test – posttest, completed with 58 subject. The sample collecting technique is at the same time with the method of quota sampling, while, the method of collecting data is completed with the questioner which is contain of the measurement of anxiety as Hamilton Anxiety Scale. The data analysis technique is using t-test. The result of the research is shows that there is differences of the rate of anxiety on the patient, before and after the therapeutic communication: the delivering information pre surgery at the orthopedic ward RSUI Kustati Surakarta. At least, it is shown with the computed of hiphotesys test completed with the significance rate as 5 % and the free degree of 57, it is shows that the result of t computed = 7,366 ttable = 2,002. However, related through the result of the research, it is suggested that the delivering information of pre surgery at the orthopedic ward RSUI Kustati Surakarta is extremely needed to be increased, at least, it is to descend the rate of patient anxiety in having surgery